Lack of detection of Middle East respiratory syndrome coronavirus in mild and severe respiratory infections in Catalonia, northeastern Spain. Issue 1 (January 2014) - Martínez, M. J.; Marcos, M. A.; Gonzalo, V.; Zboromyrska, Y.; Isanta, R.; Torner, N.; Martinez, A.; Jané, M.; Mateu, A.; Vila, J.
Abstract Surveillance of Middle East respiratory syndrome coronavirus (MERS‐CoV) was conducted to explore the possible introduction and circulation of this novel virus in Catalonia, northeastern Spain. Five hundred and sixty‐three samples from mild and severe respiratory infections collected between January 2012 and April 2013 were screened using real‐time RT‐PCR. All samples were negative, suggesting that MERS‐CoV is not circulating silently in Catalonia.